Avaliação das condições ambientais do estuário do rio Vaza-Barris (Sergipe) como uso de Crassostrea brasiliana (Lamarck, 1819) - Oliveira, Josevânia de (2019)
The Vaza-Barris river stands out due to the mangrove ecosystem that occupies a large part of its estuarine area. In this mangrove ecosystem, we find oysters of the genus Crassostrea, which play an essential biological, economic and social role. The species Crassostrea brasiliana (Lamarck, 1819), native to the Sergipe coast, has been widely used as an environmental indicator since its many characteristics make it possible to reveal the contamination of an ecosystem. This study evaluates the environmental conditions of the Vaza-Barris estuary, Sergipe, using the species C. brasiliana, and analyses the environmental and socioeconomic impacts of oyster farming and shrimp farming for coastal communities. Furthermore, we identify the socioeconomic aspects of the oyster fishermen communities in Mem de Sá (Itaporanga D'Ajuda) and Tinharé (São Cristóvão) and address the influence of salinity, pH and temperature on C. brasiliana. Through documentary research and bibliographic review, it was verified that oyster farming and shrimp farming are socioeconomically important, playing a significant role in the economy of the Northeast region. However, in order to make these activities less impacting and more profitable, it is imperative to respect the good practices, conduct training courses for producers and develop new technologies. The study of the main environmental impacts caused by marine shrimp farming on the Vaza-Barris river’s mangrove in São Cristóvão/SE was conducted using bibliographic survey; we analyze the licensing process for this activity in the area and propose environmental sustainability indicators. The main impacts caused by shrimp farming were the removal of native vegetation, inadequate management, improper effluents disposal, the introduction of exotic species and the dissemination of diseases. To address the identification of the socioeconomic aspects of the oyster fishermen communities in Mem de Sá (Itaporanga D'Ajuda) and Tinharé (São Cristóvão), we constructed semi-structured questionnaires containing topics related to individual characteristics, oyster fishing activity and the occurrence of environmental tensors in the area. The presence of small and rustic houses, low level of schooling, a high number of family members in a household, low family income and irregular garbage collection were observed both in Mem de Sá and Tinharé. Oyster fishing is mostly performed by women. The results indicate poor environmental conditions in these communities and low quality of life of their residents. Thus, the development of policies that make Oyster fishing a more sustainable and valued activity is highly needed. To evaluate the concentrations of copper, iron, zinc, manganese and lead in the tissues of Crassostrea brasiliana, oyster samples were obtained in the dry and rainy seasons at five different points located at Vaza-Barris river. It was observed that, in the dry season, a higher concentration of Zn occurred, followed by Fe, Cu, and Mn; Pb was not found. In the rainy season, Zn exhibited higher concentration, accompanied by Fe, Pb, Cu, and Mn. Copper exhibited higher levels in the dry season and was the only metal within the limits established by Brazilian legislation. The other metals exhibited higher concentrations in the rainy season, representing a risk to the environment and to the human being. The results indicate that more effective measures for physical, chemical and microbiological monitoring of the oysters' environment are needed. Lastly, we analyze the influence of salinity, pH, and temperature on Crassostrea brasiliana in Vaza-Barris river. Temperature and pH were in a favorable range for the development of C. brasiliana, although the salinity level was only within the tolerance range. All specimens were found in the adult stage and capable of sexual activity. The results indicate that C. brasiliana reproduces throughout the year in the Vaza-Barris estuary, with higher reproductive activity in months with higher temperatures and pH (October) and lower salinity levels. This thesis concludes that it is possible to evaluate the environmental health of the Vaza-Barris estuary using Crassostrea brasiliana, and we suggest measures that can reduce the environmental impacts in the area, in order to preserve this important ecosystem.